Exploiting the dynamics of eye gaze to bias intertemporal choice - Liu, Hong‐Zhi; Lyu, Xiao‐Kang; Wei, Zi‐Han; Mo, Wan‐Li; Luo, Jiong‐Rui; Su, Xiao‐Yu (Journal of behavioral decision making, 2021)
Intertemporal choices refer to decisions involving tradeoffs between costs and benefits at different times. Two types of models, namely, attribute‐ and alternative‐based models, have been developed to account for the intertemporal choices of individuals. Although behavioral evidence favors attribute‐based models, eye‐tracking data have produced mixed evidence. Examining the causal link between eye gaze and intertemporal choice may help resolve the controversy in these two intertemporal models. This study then performs a gaze‐contingent manipulation to direct the gaze time of the participants while they are choosing between two intertemporal options. The intertemporal choices of these participants were found to be biased toward a randomly determined target when their gazes were directed to the target attribute (Study 1, N = 45), but their choices were not biased when their gazes were directed to the target option (Study 2, N = 45). The gazed longer attribute also mediated the effect of gaze‐contingent manipulation on intertemporal choice. These findings suggest a causal link between intertemporal choices and the gaze‐contingent manipulation of the attribute‐based gaze pattern and contribute to the theoretical understanding of the mechanisms and processes involved in making intertemporal choices.